Voluntary Tax Compliance: Impact of Justice And Trust In Government Authorities - Nasrizal; Basri, Yesi Mutia; Rusli; azhar, Al (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to analyze the influence of the tax dimension (general justice, exchange with the government, self-interests, special provisions, tax rate structure) by using trust in government authorities as a mediating variable. The population in this study is the Individual Taxpayer in Riau Province. Sampling technique used is purposive sampling. A total of 300 questionnaires were distributed to Individual Taxpayers in the cities of Pekanbaru, Bengkalis and Bangkinang, as many as 283 data can be processed. The results of the analysis with PLS show the exchange with the government and, self-interests and the tax rate have an important effect on voluntary compliance while general justice, special povicions do not directly influence voluntary compliance. General justice that have a significant effect on trust in the government, while other variables have no effect. The results of the analysis show that trust only mediates the influence of general justice on voluntary compliance.